Rediscovering the Self Through Self-Reflection and Transformative Learning (LEARNing Landscapes, 2015)
This article explores the relevancy and potential benefits of self-reflection and reflective practice in promoting personal and professional development. In addition, it reviews the concept of transformative learning in conjunction with self-reflection since the two constructs connect to each other as well as to the process of human development. Moreover, different educational programs and activities that increase the likelihood of change and transformation are discussed. Lastly, this article concludes with my personal reflections on my learning and growth as I adapted to change and navigated new environments while studying abroad in Great Britain.
Keywords: self-reflection; professional development; transformative; learning; personal development; change; transformation